Determinasi Institusional terhadap Pengungkapan Modal Intelektual Digital pada Perguruan Tinggi Berperingkat Unirank di Indonesia - Tri Ambar Sari; Nurdian Susilowati; Christine Natalia Dewi; Salsabilla Siti Mustafiah; Vinata Puswita Sari (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2025)
This study aims to analyze the influence of institutional determination on the level of digital intellectual capital disclosure in state universities that are included in the UniRank ranking in Indonesia. In the digital era and information disclosure, the disclosure of intellectual capital (ICD) through official websites is an important indicator of institutional transparency and competitiveness. This study uses a quantitative approach with the type of associative research and total sampling of 28 state universities included in UniRank 2025. Secondary data were collected through documentation studies and analyzed using multiple linear regression with the help of SPSS. The results of the study showed that organizational complexity, internationalization, and institutional status did not have a positive effect on ICD. In fact, internationalization and the status of universities have a significant negative effect. These findings suggest that global presence and high status are not necessarily in line with a commitment to strategic information disclosure. The disclosure of intellectual capital in many universities is still symbolic and has not yet become part of an integrated institutional strategy. Therefore, clear regulations and a strong culture of transparency are needed to encourage more accountable and sustainable management of digital information.